Pengaruh Kontribusi Pajak Bumi dan Bangunan Pedesaan dan Perkotaan (PBB-P2) dan Pajak Reklame terhadap Penerimaan Pajak Daerah di Kota Bandung - Ulfa Aghniya; Yeti Apriliawati (Indonesian Accounting Research Journal, 2022)
Regional autonomy requires the Bandung City government is required to be independent by utilizing sources of income, one of wich comes from local taxes, especially from PBB-P2 and advertisement taxes. The purpose of this research is to determine partially or simultaneously the effect of the contribution of PBB-P2 and advertisement tax on local tax revenues in Bandung City in 2016-2020. The type of this research is quantitive research. The data source used is secondary data. This research uses multiple linier regression analysis method. From this study, it was found that partially PBB-P2 tax had a positive and significant effect on local taxes in Bandung City. Then partially the advertisement tax has a positive but not significant effect on local taxes in Bandung City. Furthermore, PBB-P2 and advertisement tas simultaneously have a positive and significant effect on local taxes in Bandung City.